Reliability and sensitivity of a repeated high-intensity exercise performance test for Rugby League and Rugby Union - Austin, D. J.; Gabbett, T. J.; Jenkins, D. G. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to examine the reliability and sensitivity of 3 ecologically valid repeated high-intensity exercise (RHIE) tests for professional rugby league (RL) and rugby union (RU) players. A further purpose was to investigate the relationship between RHIE performance and measures of speed (20-m sprint) and high-intensity intermittent running ability (yo-yo intermittent recovery test). Thirty-six RU and RL players were separated into 3 equal groups based on playing position: backs, RL forwards and RU forwards. Test-retest reliability was assessed by comparing total sprint time over 9 sprints during 2 identical testing sessions. The intraclass correlation coefficients (ICCs) for total sprint time were moderate to high (0.82, 0.97, and 0.94) and coefficient of variation (CV) low (4.2, 1.4, and 0.6%) for the backs, RL forwards, and RU forwards tests, respectively. However, sprint performance decrement scores were poorer, with ICC and CV of 0.78, 0.86, and 0.88 and 49.5, 48.2, and 35.8% for the backs, RL forwards, and RU forwards, respectively. Total sprint times for the backs, RL forwards, and RU forwards decreased over the 3 tests by 0.54, 0.53, and 2.09 seconds, respectively. Changes in RHIE total sprint time were moderately related to changes in 20-m sprint times (T1 to T2, r = 0.63; T2 to T3, r = 0.69; and T1 to T3, r = 0.63; all p < 0.05) but not yo-yo intermittent recovery test performances. This study has shown that the designed RL and RU RHIE tests have moderate to high reliability and produce significant improvements over a training period when total sprint times are compared.